Produce supply chain management: case study of a retail company in Minas Gerais - Veloso, Aline de Freitas; da Rocha, Denis Teixeira; de Moura, Altair Dias (Revista Gestão da Produção Operações e Sistemas, 2009)
This study aimed to investigate a retail network of produce products, through description and analysis of verti- cal arrangements, which are used to reach an appropriate level of coordination between links in the production chain. Based on the case study method, it used the theory of supply chain management to review information raised. The research focused on a company specializing in retail marketing of fruits and vegetables, present in various locations in the state of Minas Gerais. The results show the company’s adjustment of sales strategies to the four key performance factors for supply chains (stock, transportation, facilities and information), aimed at achieving a balance between efficiency and responsiveness. Efficiency in the exchange of information between the company and its head office enables it to work with minimum levels of inventory while providing new pro- ducts to customers on a daily basis. Another point is related to the location of its head office and its great bargai- ning power with suppliers that permits meeting quantity, quality and low cost for all branches in its network. Keywords: Supply Chain, produce, marketing.